The Influence of Principal Leadership and Motivation on Teacher Professionalism at Senior High School 2 Wajo - Sadri (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This study aims to determine whether the principal's leadership has a significant effect on the professionalism of State Senior High School 2 Wajo teachers. 2) The principal's leadership has a significant influence on the professionalism and motivation of State Senior High School 2 Wajo teachers. 3) Motivation has a significant effect on the professionalism of State Senior High School 2 Wajo teachers. This research was conducted at two public high schools in Wajo, which are in the Limpomajang sub-district, Majauleng sub-district, and Wajo district. The research method used is descriptive analysis (quantitative) by analyzing the influence of the principal's leadership and motivation on the professionalism of teachers at State Senior High School 2 Wajo, which amounted to 17 samples. The results showed that 1) the principal's leadership had a significant effect on the professionalism of State Senior High School 2 Wajo teachers by 88%, which was in the very good category. 2) The motivation of the principal had a significant effect on the professionalism of State Senior High School 2 Wajo teachers by 88.70%, which was in the very good category. 3) Teacher professionalism has a significant effect on the leadership motivation of the principal of State Senior High School 2, Wajo, by 91%.